Canine Tuberculosis: A Review - Barua, A. G.; Nath, P. M.; Kakoty, K.; Rajkhowa, U.; Dutta, K. J. (International Journal of Livestock Research, 2019)
Mycobacterium tuberculosis is one of a number of closely related intracellular bacterial pathogens, grouped together as the M. tuberculosis complex (MTC) which cause granulomatous disease in a broad range of host species. The genus Mycobacterium contains various obligate or opportunistic microorganisms. Mycobacterium tuberculosis, the primary agent of human tuberculosis (TB), is uncommonly isolated from cases of animal TB. However, natural infection by this pathogen can occur in a wide variety of animal hosts following close, prolonged contact with infectious humans. It is the principal cause of human tuberculosis and the extraordinary success of this pathogen is reflected by its distribution. Dogs infected with Mycobacterium tuberculosis can develop clinical tuberculosis (TB) but there are currently no validated immunological assays for diagnosing this infection in this species.TB is caused by bacteria of the Mycobacterium tuberculosis complex, mostly M. tuberculosis, but rarely also M. canetti, M. microti, M. africanum, and M. bovis. Mycobacteria are non-motile, non-spore-forming, aerobic, rod-shaped bacteria of 2–4 µm in length and possess a unique lipid-rich cell wall which gives the ‘acid-fast’ property by which they are known (acid-fast bacilli or AFBs) and renders them resistant to many disinfectants and antibiotics.Sometimes the infection doesn't cause any symptoms. This is known as latent TB.It's called active TB if one has symptoms. Most TB infected dogs do not have any signs, as the canine immune system actively suppresses the bacteria. When disease does occur common signs include weight loss, anorexia and harsh, non-productive coughing, depression, increased thirst and increased urination, diarrhea, jaundice (yellow tinge to the gums) and dehydration.